Percepatan pendapatan petani sawit melalui peningkatan kinerja pemasaran dan strategi bersaing - Enni Savitri; Riska Natariasari (Riau Journal of Empowerment, 2021)
The oil palm business is one of the businesses that can help the country's economy and help improve people's welfare. The effectiveness of SME business performance is influenced by training, organizing, utilization, and development. The target community is SMEs in Lebuh Lurus village, Inuman Kuantan Singingi sub-district. Increased marketing performance and competitive strategies can be applied to oil palm farmers with training and skill mentoring. This activity is carried out by direct counseling/discussion, discussion, and question and answer. The implementation of this activity is divided into several stages, including preparation, counseling and assistance, evaluation, and discussion. Competitive advantage, competitive intelligence, cross-functional working relationships as solutions to improving marketing performance in oil palm plantation SMEs in the province of Riau. The results of this activity teaches and administers to the oil palm smallholders in implementing competitive strategies and marketing palm oil products. Training for human resource oil palm workers and the creation of agricultural counseling programs.